Teaching Business Presentations: Coping With Linguistic Anxiety (the Case Of Engineers In The Algerian Hydrocarbon Sector) - Zineb Chaalane (Al-Lisaniyyat)
The objective of this research is to investigate the effect of linguistic anxiety on the language proficiency in Business presentations among the Algerian engineers working in the hydrocarbon sector; British Petroleum/Sonatrach/Statoil Joint Venture is the case of study of the intended research. The second objective is to design a business presentation syllabus that responds to their language proficiency deficits. The empirical study is implemented through a Present Situation Analysis and a questionnaire. The Present Situation Analysis focuses on the English taught in the Joint Venture and the engineers’ job description in order to find out the most needed language skill. The questionnaire is administered to the engineers to examine their lacks and wants in terms of language in Business presentations. We came across the fact that the engineers’ lacks rests on three key aspects of language proficiency; grammar, lexis and language of structure. The suggested syllabus lied on the compromise of three approaches: the genrebased approach, the task-based approach and the integrated skills approach